Vitamin D Inhibits IL-6 Pro-Atherothrombotic Effects in Human Endothelial Cells: A Potential Mechanism for Protection against COVID-19 Infection? - Giovanni Cimmino; Stefano Conte; Mariarosaria Morello; Grazia Pellegrino; Laura Marra; Andrea Morello; Giuseppe Nicoletti; Gennaro De Rosa; Paolo Golino; Plinio Cirillo (Journal of Cardiovascular Development and Disease, 2022)
Background: Thrombosis with cardiovascular involvement is a crucial complication in COVID-19 infection. COVID-19 infects the host by the angiotensin converting enzyme-2 receptor (ACE2r), which is expressed in endothelial cells too. Thus, COVID-related thrombotic events might be due to endothelial dysfunction. IL-6 is one of the main cytokines involved in the COVID-19 inflammatory storm. Some evidence indicates that Vitamin D (VitD) has a protective role in COVID-19 patients, but the molecular mechanisms involved are still debated. Thus, we investigated the effect of VitD on Tissue Factor and adhesion molecules (CAMs) in IL-6-stimulated endothelial cells (HUVEC). Moreover, we evaluated levels of the ACE2r gene and proteins. Finally, we studied the modulation of NF-kB and STAT3 pathways. Methods: HUVEC cultivated in VitD-enriched medium were stimulated with IL-6 (0.5 ng/mL). The TF gene (RT-PCR), protein (Western blot), surface expression (FACS) and procoagulant activity (FXa generation assay) were measured. Similarly, CAMs soluble values (ELISA) and ACE2r (RT-PCR and Western blot) levels were assessed. NF-kB and STAT3 modulation (Western blot) were also investigated. Results: VitD significantly reduced TF expression at both gene and protein levels as well as TF-procoagulant activity in IL-6-treated HUVEC. Similar effects were observed for CAMs and ACE2r expression. IL-6 modulates these effects by regulating NF-κB and STAT3 pathways. Conclusions: IL-6 induces endothelial dysfunction with TF and CAMs expression via upregulation of ACE2r. VitD prevented these IL-6 deleterious effects. Thus, it might be speculated that this is one of the hypothetical mechanism(s) by which VitD exerts its beneficial effects in COVID-19 infection.